COGNITIVE MODELING OF KNOWLEDGE MANAGEMENT MECHANISMS IN THE TRAINING OF SPECIALISTS - Liubava Chernova; Lyudmyla Chernova (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject of research in this article is knowledge management in the training of specialists in project-oriented organizations, in particular, higher education institutions. The purpose of the work is to develop a cognitive model of knowledge management for the formation of educational programs in the training system. Objectives of the study: to consider the concepts and mechanisms of knowledge management of organizations; to form a cognitive model of the knowledge management mechanism; to consider system indicators of cognitive model; to analyze the structural features of the cognitive model. The following methods are used in the work: project management methodology (knowledge management areas), system approach, cognitive and graph models. Results. The article provides a definition of "knowledge management", discusses the conditions under which the necessary knowledge and information will be available to perform tasks. The issue of consideration the specifics and features of the educational institution is discussed. Knowledge management methods are used in the construction of the educational process at the university. The main functions in the practical activities of the organization are given: mediation, export, internalization, cognition. Forms of practical implementation of knowledge management are also considered: educational organization, knowledge library and strategic awareness. The article also considers the possibility of the main provisions of the theory of knowledge management in the educational process, as improving the quality of training is the goal of any educational system. The article develops a cognitive model of the knowledge management mechanism, on the basis of cognitive analysis revealed useful patterns that reflect the influence of factors of different physical nature on the results of training. Conclusions. Cognitive modeling can be the key to rapidly improving the effectiveness of knowledge management in training. The classical approach to knowledge management requires a high level of employee involvement in relevant processes, as they need to identify knowledge, share it, record it and apply it. Cognitive modeling can reduce this requirement as it streamlines the processes of identifying, capturing, storing, and sharing knowledge. In addition, they increase the applicability of knowledge by offering appropriate context for the student. The accumulated experience of cognitive modeling of complex organizational management systems allows on a fundamental basis to approach the study of knowledge management mechanisms in the training of specialists. It is proposed to use the obtained results to configure knowledge management mechanisms in order to improve the quality of training.